Metagenome-wide association study revealed disease-specific landscape of the gut microbiome of systemic lupus erythematosus in Japanese. Issue 12 (23rd August 2021) - Tomofuji, Yoshihiko; Maeda, Yuichi; Oguro-Igashira, Eri; Kishikawa, Toshihiro; Yamamoto, Kenichi; Sonehara, Kyuto; Motooka, Daisuke; Matsumoto, Yuki; Matsuoka, Hidetoshi; Yoshimura, Maiko; Yagita, Mayu; Nii, Takuro; et al.
Abstract : Objective: Alteration of the gut microbiome has been linked to the pathogenesis of systemic lupus erythematosus (SLE). However, a comprehensive view of the gut microbiome in SLE and its interaction with the host remains to be revealed. This study aimed to reveal SLE-associated changes in the gut microbiome and its interaction with the host by a comprehensive metagenome-wide association study (MWAS) followed by integrative analysis. Methods: We performed a MWAS of SLE based on shotgun sequencing of the gut microbial DNA from Japanese individuals ( N case =47, N control =203). We integrated the result of the MWAS with the genome-wide association study (GWAS) data and plasma metabolite data. Results: Via species level phylogenetic analysis, we identified and validated increases of Streptococcus intermedius and Streptococcus anginosus in the patients with SLE. Microbial gene analysis revealed increases of Streptococcus -derived genes including one involved in redox reaction. Additionally, microbial pathways related to sulfur metabolism and flagella assembly were altered in the patients with SLE. We identified an overlap in the enriched biological pathways between the metagenome and the germline genome by comparing the result of the MWAS and the GWAS of SLE (ie, MWAS-GWAS interaction). α-diversity and β-diversity analyses provided evidence of dysbiosis in the metagenome of the patients with SLE. Microbiome-metabolome association analysis identified positive dosage correlation of acylcarnitine with Streptococcus intermedius, an SLE-associated taxon. Conclusion: Our MWAS followed by integrative analysis revealed SLE-associated changes in the gut microbiome and its interaction with the host, which contribute to our understanding of the relationship between the microbiome and SLE.